2011
DOI: 10.1007/s12298-011-0066-6
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response of Cannabis sativa L., an important medicinal plant, to elevated levels of CO2

Abstract: The effect of elevated CO 2 concentrations (545 and 700 μmol mol −1 ) on gas exchange and stomatal response of four high Δ 9 -THC yielding varieties of Cannabis sativa (HPM, K2, MX and W1) was studied to assess their response to the rising atmospheric CO 2 concentration. In general, elevated CO 2 concentration (700 μmol mol ) significantly (p<0.05) stimulated net photosynthesis (P N ), water use efficiency (WUE) and internal CO 2 concentration (C i ), and suppressed transpiration (E) and stomatal conductance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…The present study also indicated that the value of κ 2LL may differ among growth environments. Thirdly, variation in photosynthetic competence among cultivars has been reported for hemp (Chandra et al ., ). As only one cultivar was studied, it is not clear whether the advantage of photosynthetic competence of hemp is persistent across cultivars.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study also indicated that the value of κ 2LL may differ among growth environments. Thirdly, variation in photosynthetic competence among cultivars has been reported for hemp (Chandra et al ., ). As only one cultivar was studied, it is not clear whether the advantage of photosynthetic competence of hemp is persistent across cultivars.…”
Section: Discussionmentioning
confidence: 97%
“…Chandra et al . (, ,b, ) showed the response of leaf photosynthesis of hemp to irradiance intensity, CO 2 concentration and temperature by measuring gas exchange of leaves from glasshouse‐grown plants. Marija et al .…”
Section: Introductionmentioning
confidence: 99%
“…Our studies show that cannabis exhibits higher rate of photosynthesis at high photosynthetic photon flux density (PPFD,~1500 µmolm 2 s -1 ), which is typically sunny summer day in Mississippi (Chandra et al, 2008;Chandra et al, 2015). Further, about a 50% increase in the rate of photosynthesis was observed under doubling of CO 2 concentration as compared to ambient CO 2 concentration (Chandra et al, 2008;Chandra et al, 2011b). Higher humidity is generally~60-75% is recommended at the young vegetative stage of plants whereas a lower range of 50 to 55% is recommended during the flowering stage.…”
Section: Vegetative Propagationmentioning
confidence: 72%
“…(1987) reported that supplementing with UV-B radiation for 3 h daily increased THC concentrations on C. sativa leaves and buds, whereas supplementing with UV-C radiation (100–280 nm) influenced resveratrol and piceid levels (Marti et al., 2014). Photosynthetic responses in C. sativa were measured at different light intensities, temperatures, and CO 2 concentrations (Chandra et al., 2008, 2011a, 2015). Of the environmental conditions tested, the highest net photosynthetic rates occurred at 30°C and 1,500 μmol m −2 s −1 , but this was reduced by nearly 20% when intensity increased to 2000 μmol m −2 s −1 ; no declined trend was observed at any other test temperatures (Chandra et al., 2008).…”
Section: Electrical Lighting Systemsmentioning
confidence: 99%